TELA'AH PEMIKIRAN HADITS JOSEP SCHACHT DALAM BUKU THE ORIGIN OF MUHAMMAD JURISPRUDENCE, DAN AN INTRODUCTION TO ISLAMIC LAW - Paizin, Harel Bayu (Jurnal Studi Hadis Nusantara, 2023)
This article discusses the thinking of one of the orientalist figures who is quiteconcerned and popular in the hadith studies namely Josep Schacht. He concludedthat the hadith was false and was made by para tabi'in. To prove the truth of thehypothesis, he raises three very well-known theories, namely argumentum siliento,projecting back, and common links. Many people responded to the position of theresearch and many also rejected it, both from Muslim scholars and western scholars.This paper focuses on the discussion of two books which were the masterpieces hewrote, namely The Origin of Muhammad Jurisprudence (1950), and An Introductionto Islamic Law (1964, and the theory offered by Schacht to prove the truth of theHadith of Prophet Muhammad SAW.